DMTMM-mediated amidation of alginate oligosaccharides aimed at modulating their interaction with proteins. (15th March 2018) - Labre, Flavien; Mathieu, Sophie; Chaud, Patricia; Morvan, Pierre-Yves; Vallée, Romuald; Helbert, William; Fort, Sébastien
Highlights: DMTMM promoted efficient amidation of alginate oligosaccharides (AOS). AOS were functionalized with amino acids and carbohydrates. Grafting conferred improved stability to AOS against alginate lyases. Mannose-grafted AOS exhibited multivalent inhibition of Con A lectin. Abstract: Alginate oligosaccharides (AOS) with a weight average molecular weight of 5 kDa were efficiently amidated with amino acids and carbohydrates in aqueous media in the presence of 4-(4, 6-dimethoxy-1, 3, 5-triazin-2-yl)-4-methylmorpholinium chloride (DMTMM). Here, alanine, leucine, serine, as well as mannose and rhamnose, were amidated at high yields with a good control of the degree of substitution (DS). Amino acid- and carbohydrate-grafted AOS showed improved stability against degradation by alginate lyases having different specificities. This enzyme resistance was correlated with the DS: hydrolysis was reduced by 60–70% for low DS (0.1), whereas AOS with DS ranging from 0.4 to 0.6 remained unhydrolyzed. Competitive inhibition assays demonstrated multivalent binding of mannose-amidated AOS to concanavalin A lectin. A 178-fold affinity enhancement was observed for AOSMan-0.38 (DS 0.38) over α-methyl-mannoside with an IC50 of 5.6 μM, lending further evidence for the promising potential of AOS as multivalent scaffolds.